Ferns of Malaysian rain forest: a journey through the fern world - Yusuf, Umi Kalsom (Universiti Putra Malaysia Press, 2010)
Ferns are seedless vascular plants which differ from gymnosperms and flowering plants as they do not have either seeds or flowers but reproduce via spores. They have many features similar to mosses and algae but are usually differentiated from these simpler plants as they have xylem and phloem for the conduction of water and food materials. They are most commonly found in moist, shady forest, crevices in rock faces, and also grow in arctic and alpine tundra, saline mangrove swamps, semiarid deserts and on coastal rocks. The greatest number of fern species can be found in the tropics of both hemispheres. It was estimated that about 10500-11300 of the fern species have been described and 1165 species were recorded in the tropical rain forest of Malaysia. This lecture discusses the morphological diversity, anatomy and cytology of Malaysian rain forest ferns. Selected research works on morphology, anatomy and cytology of these ferns are reviewed. The economic importance of ferns as food, medicine, fibre, craft, fuel and building materials is also discussed. In addition, a number of comprehensive studies on the chemistry and biological activities in ferns are also reviewed. Apart from exploitation of fern taxa for their significant scientific documentation and economic value, the awareness on their conservation status is also emphasized.